2005
DOI: 10.1038/nature03236
|View full text |Cite
|
Sign up to set email alerts
|

Effective leadership and decision-making in animal groups on the move

Abstract: For animals that forage or travel in groups, making movement decisions often depends on social interactions among group members 1,2 . However, in many cases, few individuals have pertinent information, such as knowledge about the location of a food source 3,4 , or of a migration route [5][6][7][8][9] . Using a simple model we show how information can be transferred within groups both without signalling and when group members do not know which individuals, if any, have information. We reveal that the larger the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

75
2,070
10
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 2,389 publications
(2,166 citation statements)
references
References 20 publications
75
2,070
10
11
Order By: Relevance
“…Computational models of bird flocking build on the combination of three simple behavioural rules, namely repulsion from near individuals, movement towards far neighbours and alignment with average velocities of neighbours 76 . Remarkably, these rules can also account for hierarchical flocking without explicit signalling of experienced agents 77 . However, perceiving the position of other flying drones is still very challenging.…”
Section: Review Insightmentioning
confidence: 99%
“…Computational models of bird flocking build on the combination of three simple behavioural rules, namely repulsion from near individuals, movement towards far neighbours and alignment with average velocities of neighbours 76 . Remarkably, these rules can also account for hierarchical flocking without explicit signalling of experienced agents 77 . However, perceiving the position of other flying drones is still very challenging.…”
Section: Review Insightmentioning
confidence: 99%
“…Further experiments using 475 shoals of zebrafish should be completed to assess whether navigation is 476 facilitated by collective decision-making in this species (Couzin et al 2005). 477…”
Section: (Zebrafish) 344mentioning
confidence: 99%
“…A long-range interaction has been incorporated into the SPP model (Mikhailov and Zanette, 1999), and continuum, "hydrodynamic" versions of this model have been introduced Tu, 1995, 1998;Topaz et al, 2006). Recently, Couzin et al (2002Couzin et al ( , 2005) have introduced a model to provide insights into the mechanism of decision making in biological systems, which reproduces many important observations made in the field, and provides new insights into these phenomena. A review for various models can be found in Parrish et al (2002) and Czirók and Vicsek (2001).…”
Section: Introductionmentioning
confidence: 99%